2013
DOI: 10.1016/j.clinthera.2013.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Assessment of Diabetic Foot Ulcer Debridement with Collagenase: Results of a Randomized Controlled Study

Abstract: CCO treatment provides equivalent debridement of DFUs similar to SMG while fostering better progress toward healing as measured by decreasing wound area over time and improved response rates at the end of follow-up. In addition, CCO yields a more favorable cost-effectiveness ratio in both the physician office and hospital outpatient department settings of care. ClinicalTrials.gov identifier: NCT01056198.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 33 publications
4
59
0
4
Order By: Relevance
“…Only CCO treatment resulted in a statistically significant decrease from baseline in the mean future science group www.futuremedicine.com wound area at the end of treatment (-44.9%; p = 0.0164) and at the end of follow-up (-53.8%; p = 0.012) [40]. Corresponding changes for the SMG group were +0.8 and +8.1%.…”
Section: Discussion Of Clinical Effectivenessmentioning
confidence: 91%
See 2 more Smart Citations
“…Only CCO treatment resulted in a statistically significant decrease from baseline in the mean future science group www.futuremedicine.com wound area at the end of treatment (-44.9%; p = 0.0164) and at the end of follow-up (-53.8%; p = 0.012) [40]. Corresponding changes for the SMG group were +0.8 and +8.1%.…”
Section: Discussion Of Clinical Effectivenessmentioning
confidence: 91%
“…Cost-effectiveness of CCO in DFU Two cost analyses of CCO debridement in patients with DFU also yielded estimates favoring CCO over alternative debridement methods [40,53]. In an analysis of results from a randomized, open-label trial of 55 patients with DFU using a three-state Markov model, Motley et al calculated that the number of epithelialized weeks was 25% greater in patients treated with the CCO plus serial sharp debridement (35 weeks) versus other debridement methods (28 weeks) [39,53].…”
Section: Discussion Of Economic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Tallis et al (2013) showed that the collagenase ointment is tolerable and clinically effective in providing non-viable tissue removal and allow effective scar [16].…”
Section: Discussionmentioning
confidence: 99%
“…A capacidade de decompor o colágeno sem afetar as propriedades de outras proteínas, tornou a colagenase uma ferramenta aplicável nas ciências médicas para limpar feridas necrosadas, escaras, cicatrizes pós-operatórias, em queimaduras, no tratamento de psoríase e pediculoses, em casos de implantes e perdas ósseas, em casos de lesões de mamilos de mulheres em aleitamento, no tratamento de cicatrizes hipertróficas, no tratamento de fibroma uterino, de isquemias do coração, de glaucoma, no reparo de cartilagem, de queloides, no de hérnia de disco intervertebral, no da celulite, no debridamento de úlceras de pessoas diabéticas e na regeneração dos tecidos da pele (Takahashi et al, 1999, Özcan et al, 2002, Watanabe, 2004, Arakawa et al, 2012, Alipour et al, 2016, Tallis et al, 2013, Brunengraber et al, 2014, Chandika et al, 2015.…”
Section: Aplicações Na Indústria Biomédica E Terapêuticaunclassified